2020
DOI: 10.3393/ac.2020.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparative Analysis of the Incidence of Vasovagal Reaction and the Effect of Rectal Submucosal Lidocaine Injection in Stapled Hemorrhoidopexy: A Randomized Controlled Trial

Abstract: A c c e p t e d A r t i c l e 0 ABSTRACT Purpose To evaluate the incidence of vasovagal reactions (VVRs) and the efficacy of a lidocaine injection to prevent its occurrence. MethodsPatients (n=117) diagnosed with hemorrhoids and scheduled to undergo a stapled hemorrhoidopexy (SH) were randomly divided according to the submucosal injection used on the rectum into: lidocaine (n=53, lidocaine injected just before full closure of the stapler) and control groups (n=58). Outcomes compared included baseline patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…If possible, surgical procedures should be delayed until a few weeks after delivery. It would be advantageous to avoid potential complications associated with hemorrhoidectomy [18,19].…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…If possible, surgical procedures should be delayed until a few weeks after delivery. It would be advantageous to avoid potential complications associated with hemorrhoidectomy [18,19].…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…In the SH, there are few papers about the prevalence or prevention method of VVR that occurs during surgery. Cho et al [ 14 ] reported a randomized control trial of incidence VVR and the effect of lidocaine injection during SH. A total of 111 patients were included in this study and 20 patients had low abdominal pain during SH.…”
mentioning
confidence: 99%
“…Abdominal pain or VVR may be associated with a pulled mucosa in process of SH. In this study, the results were not compared according to the surgical method [ 14 ]. However, in the case of partial SH, selectively pure-string sutures were done to only the hemorrhoidal tissues preserving normal tissue [ 15 ].…”
mentioning
confidence: 99%